An empirical study of perceived service quality of Islamic banks: a comparison between Malaysia and Kuwait - Mohd Shariff, Ros Aniza; Asutay, Mehmet; Al-Adwani, Tahani (Gerlach Press, Berlin, Germany, 2015)
Purpose – The purpose of this research is to provide a comparison study of service quality among the customers of Islamic banks between two nations: Malaysia vs. Kuwait. The study investigated how service quality affects customer satisfaction by assessing the magnitude of the relationship between selected variables. This study is crucial due to the development of Islamic banking industry, and the growing concern on service quality issues among various players in the industry particularly in Malaysia and the GCC region. Design/methodology/approach – The paper compare the service quality ratings by the customers of Islamic banks in Malaysia and Kuwait. It also examined the relationship of customer satisfaction with the modified SERVQUAL dimensions. Questionnaires were distributed to 600 respondents in Malaysian and 700 respondents in Kuwait. A descriptive analysis and Multiple Regression analysis were utilised to compare the ratings of customer service quality and the customers’ satisfaction of these two nations. Findings – The paper finds significant differences in the ratings of service quality dimension provided by these two countries with respect to the ranking of the most important SERVQUAL dimension and the customers’ satisfaction relationship with SERVQUAL dimensions. The results suggest that the difference in ratings of service quality and the customers’ satisfaction of these two countries was because their customers have a unique nature; different cultures and traditions. Thus, they need different approach to address the demands of their customers. Research limitations – The survey subjects were customers of Islamic banks in Malaysia and Kuwait. By expanding the total number of surveys to include more countries and regions, this research could provide additional insight into the Islamic banking service quality and customer satisfaction. Originality – This research attempts to fill the gaps in the existing body of knowledge by providing insights into service quality of Islamic banks in Malaysia and to compare it with one of the country in GCC (Kuwait). In addition, the attitude of the customers will be a good indicator for the trend of Islamic banking service quality in the future. Different cultures and social backgrounds will also play a role in the development of Islamic banking industry in both nations and globally. Keywords– Service Quality, Customer Satisfaction, Malaysia, Kuwait, Islamic Banks.